The fight against stigma: Multilevel stigma interventions in schizophrenia patients - Adang Bachtiar; Heni Dwi Windarwati; Budi Anna Keliat; Raden Irawati Ismail; Niken Asih Laras Ati; Ari Dwi Sulaksono; Shofi Khaqul Ilmy (SAGE Publishing, 2020)
Background: Stigma is one of the main factors causing pasung (physical restraint or confinement in Indonesian terms) in schizophrenia patients. It is the main obstacle to reducing the number of pasung throughout the world. Thus, there is a need for appropriate interventions to reduce stigma in schizophrenia patients who go through pasung. This study aims to identify multilevel stigma interventions in people with schizophrenia who go through pasung (physical restraint and confinement). It can be applied and adapted to various cultural contexts.  Design and Methods: Quasi-experimental research with pretest and post-test analysis consists of 82 people with schizophrenia who go through pasung. Respondents were divided into the intervention group and the control group. A multilevel stigma intervention was given to the intervention group for three months. Results: There was a significant difference in the average stigma score in the control group (moderate category stigma) and the intervention group (mild category stigma) after multilevel stigma intervention (p-value = 0.04). The average stigma score of schizophrenia patients in the intervention group decreased by 8.2%, while the average stigma score in the control group increase of 20.4%. Conclusions: Multilevel stigma interventions are effective in reducing stigma in people with schizophrenia who go through pasung. We underline that multilevel stigma interventions through collaboration from various parties can provide great opportunities in stigma reduction programs in people with schizophrenia who go through pasung.